2022
DOI: 10.3389/fmed.2022.914016
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Lipid Metabolism: Implications for Systemic Lupus Erythematosus and Cardiovascular Disease Risk

Abstract: It is known that healthy women during childbearing years have a lower risk of cardiovascular disease (CVD) and coronary heart disease compared to age matched men. Various traditional risk factors have been shown to confer differential CVD susceptibilities by sex. Atherosclerosis is a major cause of CVD and mortality and sex differences in CVD risk could be due to reduced atherogenic low and very low-density lipoproteins (LDL and VLDL) and increased atheroprotective high density lipoproteins (HDLs) in women. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 104 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…However, there are serious differences in the metabolism of cholesterol between men and women, that seem to result in other differences in the disease course. 71 Studies among the US population, it was revealed that total cholesterol is higher among white women, in both sexes among blacks and Asians, and Hispanic women. 72 Moreover, the composition of lipid profiles is also different in men and women.…”
Section: Lipid Metabolism Differencesmentioning
confidence: 99%
“…However, there are serious differences in the metabolism of cholesterol between men and women, that seem to result in other differences in the disease course. 71 Studies among the US population, it was revealed that total cholesterol is higher among white women, in both sexes among blacks and Asians, and Hispanic women. 72 Moreover, the composition of lipid profiles is also different in men and women.…”
Section: Lipid Metabolism Differencesmentioning
confidence: 99%